Corporate Criminal Liability for Criminal Acts of Corruption - Muhammad Ridwan Lubis; Panca Sarjana Putra; Yasmirah Mandasari Saragih (UNISSULA, 2021)
The practice of this criminal act of corruption that involves corporations is an extraordinary crime and is very detrimental to the state. The direct consequences of these crimes to society are financial losses, job losses, and even loss of life due to the crisis. Researchers use normative juridical research methods with 3 (three) approaches to examine two problems discussed with normative research methods. It was found that corporate crime against corruption contained five theories of strict liability according to the law (strict liability) where historically the law began to pay more attention and the principle of absolute responsibility as a punishment needed to prevent retaliation then changed. be a responsibility based on the element of error